2002
DOI: 10.4064/aa105-2-4
|View full text |Cite
|
Sign up to set email alerts
|

On the irreducibility of the generalized Laguerre polynomials

Abstract: Let m ≥ 1 and a m be integers. Let α be a rational number which is not a negative integer such that α = u v with gcd(u, v) = 1, v > 0. Let φ(x) belonging to Z[x] be a monic polynomial which is irreducible modulo all the primes less than or equal to vm + u. Let a i (x) with 0 ≤ i ≤ m − 1 belonging to Z[x] be polynomials having degree less than deg φ(x). Assume that the content of (a m a 0 (x)) is not divisible by any prime less than or equal to vm + u. In this paper, we prove that the polynomialsb j a j (x)φ(x)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…It is still an unsolved question whether the Legendre polynomials are irreducible over the rationals, see [23], [24], [30], [40] and [41]. H. Ille has shown that P (0;0) n (x) has no quadratic factors which implies that P (0;0) n p b=c 6 = 0 for all n; b; c 2 N (even for the case b = 1; 3): In passing we note that recent research is devoted to the study of irreducibility of the Laguerre polynomials L n (x) initiated by I. Schur, see [20], [22], [36], and for a family of Jacobi polynomials see [12]. For general questions about irreducibility of polynomial with rational coe¢ cients we refer to [28], [31] and [38].…”
Section: The Main Resultsmentioning
confidence: 99%
“…It is still an unsolved question whether the Legendre polynomials are irreducible over the rationals, see [23], [24], [30], [40] and [41]. H. Ille has shown that P (0;0) n (x) has no quadratic factors which implies that P (0;0) n p b=c 6 = 0 for all n; b; c 2 N (even for the case b = 1; 3): In passing we note that recent research is devoted to the study of irreducibility of the Laguerre polynomials L n (x) initiated by I. Schur, see [20], [22], [36], and for a family of Jacobi polynomials see [12]. For general questions about irreducibility of polynomial with rational coe¢ cients we refer to [28], [31] and [38].…”
Section: The Main Resultsmentioning
confidence: 99%
“…[10], [11], and Hajir-Wong [12]. In particular, we have the following theorem of Filaseta and Lam [4] on the irreducibility of GLP.…”
Section: Introductionmentioning
confidence: 98%
“…conditions ii) and iii) of Lemma 3.1 hold. By Filaseta-Lam [4], there is an effectively computable constant N (α) such that f (x) is irreducible for n ≥ N (α). Thus, all the conditions of Lemma 3.1 hold, and the proof of the theorem is complete.…”
Section: Proof Of Theorem 11mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many recent results that provide irreducibility conditions for various classes of polynomials by using techniques coming from valuation theory (see for instance [23], [24], [2], [3], [4], [8], [5] and [9]), or Newton polygon method (see for instance [12], [13], [14], [15], [16], [17], [18], [1], [6], [7], [22] and [25]). …”
Section: Introductionmentioning
confidence: 99%